La isla durmiente - Martín de los Santos, David (Spain : de los Santos, David Martin, 2005)
llusion, hopes, and faith are weapons that we create to survive in the face of adversity.Religion, superstition and art are spaces where we can develop the concepts created by our imagination to fight suffering.The Cuban citizen is a dreamer, and this film attempts to make a trip towards a real Cuba, as real as its dreams.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films